Nuevo aporte al conocimiento sobre la redacción del control δ de las ánforas dressel 20 del Monte Testaccio en la modificación antoniniana: el refrendo en δ de la cifra escrita en la posición α - Pérez González, Jordi; Heredero Berzosa, Javier; Aguilera Martín, Antonio José (Collectanea Philologica, 2022)
Within the complex system that once formed part of the epigraphic ensemble that accompanied these amphorae, we highlight the particular study of the painted marks known as tituli picti in the delta position of the olive oil amphorae from Baetica, Dressel 20. Here we address a singular fact, only detectable through the visualization of large data sets, indicating the existence of the endorsement in delta of the amount expressed in alpha throughout the years of the Antonine reform. If until now it was believed to be something fortuitous, or a scribeʼs error, now it could be considered, due to its structure and the cases exposed, a regulated script.